MAPPING OF FOOD CROPS COMMODITY IN SIDOARJO REGENCY - Listin Fitrianah (Geographica: Science and Education Journal, 2021)
First step towards agricultural development that is based on the concept of efficiency to gain a comparative and competitive advantage in the face of competition both at regional and global levels. Geographic Information System program so that the distribution of food crop commodities in Sidoarjo Regency is obtained. The data analysis in this study includes the identification of the potential and characteristics of the basic commodity agribusiness which is carried out to determine the potential of the base commodity using the Location Quotient (LQ) method. The sub-district which is considered superior for food crop commodities is Prambon District with its food crops, namely rice, corn, green beans and soybeans. The LQ value for food crops is one basic commodity in Sidoarjo Regency, namely is paddy.